Bridging the technology-gap in economic transition, the J-curve of growth and unemployment - Pascal Hetze (Universität Rostock, Institut für Volkswirtschaftslehre, 2006)
The macroeconomic experience has been somewhat ambiguous during the historic experiment of economic transition in the former centrally-planed countries in Central and East Europe (CEE). The economic restructuring produced a notable catching-up in terms of productivity but also a J-curve shape of output growth accompanied by an increase in unemployment on a large scale. This paper models the transformation progress which leads to these contradictory outcomes. Before transition initiated catching-up, the economies suffered from two limits to growth: a gap of usable capital and a gap of technologies. Accordingly, a rapid technology transfer from the advanced Western economies led to a significant technological and structural change combined with high rates of labor reallocation. If we include frictions in the consequent matching between job seekers and jobs, the model reproduces the pattern of productivity, growth and unemployment that we find in the CEE countries.
Keywords: E24; O33; P20; 330; catching-up; growth; unemployment; technological change; transition economies